2013
DOI: 10.1021/jm3012917
|View full text |Cite
|
Sign up to set email alerts
|

Development of New Cyclic Plasmin Inhibitors with Excellent Potency and Selectivity

Abstract: The trypsin-like serine protease plasmin is a target for the development of antifibrinolytic drugs for use in cardiac surgery with cardiopulmonary bypass or organ transplantations to reduce excessive blood loss. The optimization of our recently described substrate-analogue plasmin inhibitors, which were cyclized between their P3 and P2 side chains, provided a new series with improved efficacy and excellent selectivity. The most potent inhibitor 8 binds to plasmin with an inhibition constant of 0.2 nM, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 58 publications
2
69
0
Order By: Relevance
“…Aprotinin, a plasmin inhibitor in limited use in some countries, also suffers from a lack of specificity [1,5,6]. Several plasmin inhibitors being developed as antifibrinolytics include KDI-L17R [15] textilinin-1 [16] and cyclic peptidomimetics [13,14]. Yet, these are active site inhibitors and their selectivity for plasmin is challenging because of the similarity of active site geometries of a number of trypsin-like proteases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aprotinin, a plasmin inhibitor in limited use in some countries, also suffers from a lack of specificity [1,5,6]. Several plasmin inhibitors being developed as antifibrinolytics include KDI-L17R [15] textilinin-1 [16] and cyclic peptidomimetics [13,14]. Yet, these are active site inhibitors and their selectivity for plasmin is challenging because of the similarity of active site geometries of a number of trypsin-like proteases.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches include substrate-based design of linear and cyclic peptidomimetics [10][11][12][13][14], mutagenesis of key residues to engineer Kunitz-and Kazal-type protein/peptide inhibitors [15][16][17], covalent inhibition through a reactive nitrile or aldehyde warhead [18,19], and structure-based computational inhibitor design [20,21]. Each of these approaches typically targets the enzyme's active site.…”
Section: Rationale For Screening a Focused Library Of Sulfated Small mentioning
confidence: 99%
See 1 more Smart Citation
“…A relatively strong trypsin inhibition was still found for the phenylsulfonyl and cyclohexylsulfamoyl analogues 29 and 31, with K i values of 62 and 21 nM, respectively, which is in the same range as found for the reference compounds 2 and 3 ( Table 2). 25,27 The strong subnanomolar inhibitory potency of compounds 3, 29, and 31 suggested that plasmin should tolerate some P1 modifications, which lead to a generally reduced affinity against all trypsin-like serine proteases. Therefore, additional inhibitors with the longer piperazine-dipropionyl linker have been prepared, which provided slightly more potent inhibitors than the shorter piperazine-diacetyl linker.…”
Section: Synthesismentioning
confidence: 99%
“…In contrast, no cleavage could be observed after the P2 lysine, because the reference 2,4-dichlorophenylacetyl-Lys-Lys-OH is more hydrophilic and elutes at 25.95 min. Moreover, under identical conditions approximately 42% of the known chromogenic trypsin substrate methylsulfonyl-D-cyclohyexylalanine-Gly-Arg-pnitroanilide 84 was hydrolyzed after the P1-Arg residue.…”
Section: Stability Test With Trypsinmentioning
confidence: 99%